Mexico's Approach to Quality Assurance - El-Khawas, Mohammed; El-Khawas, Elaine (International Higher Education, 1998)
The last decade has seen substantial growth throughout the world in higher education quality assurance systems. As one knowledgeable observer notes, more than 50 agencies now exist worldwide that have roles related to quality assessment or quality assurance.1 In most cases, these agencies have been mandated by government decrees and follow a design developed by ministry officials. Often these agencies have encountered resistance or criticism. In other instances, their approach has had to be revised extensively— or even disbanded—after a short time. By the late 1980s, Mexican institutions of higher education were in dire need of additional funding. The financial crisis of the 1980s caused a 50 percent decline in the purchasing power of faculty salaries, forcing many qualified academics to quit their jobs or to take on additional employment. This resulted in severe staffing problems and a deterioration in teaching conditions at a time of increasing enrollments. This led to public concern and government demands for improving the quality of higher education. With the economic recovery in the late 1980s, the government was ready to increase public expenditures on higher education but insisted on reforms and increased public accountability.